Finnish pre-service primary and science teachers’ motivations to enrol into teacher education and their perceptions of teaching - Lehtinen, Antti; Veermans, Koen; Jaakkola, Tomi (Informa UK Limited, Taylor & Francis Group, 2025)
In Finland, primary teacher education is highly competitive, while secondary science teacher education struggles to fill positions. However, both fields experience turnover. This study investigates the motivations for enroling in teacher education and perceptions of teaching among Finnish pre-service primary and science teachers, using the FIT-Choice scale and interviews for data. Similarities and differences in motivations and perceptions of teaching were found. The intrinsic value of teaching was the strongest motivation for both groups. Pre-service primary teachers were more motivated by altruism and a desire to work with children, while science teachers indicated stronger perception of teaching as a well-paid career. Additional motivations outside the FIT-Choice included family members working as teachers, moving away from a scientific career, the ability to work in other occupations and a desire for an active and social occupation. Addressing turnover benefits from enabling teachers to fulfil their motivations for enroling in teacher education.